Endoscopic resection of subtotal or completely circumferential laterally spreading colonic adenomas: technique, caveats, and outcomes - Tutticci, Nicholas; Klein, Amir; Sonson, Rebecca; Bourke, Michael J. (Endoscopy, 2016)
Background and study aims: Endoscopic mucosal resection (EMR) is an established treatment for large (≥ 20 mm) laterally spreading lesions (LSLs). LSLs with complete or subtotal (> 90 %) circumferential extent (C-LSLs) are generally referred for surgery. Data on technique, efficacy, and safety of EMR for these lesions are absent. The aim of this study was to describe the technique and long-term outcomes of EMR for C-LSLs.Patients and methods: Prospective observational study of consecutive patients referred for EMR of LSL at a tertiary care center over 63 months to April 2015. Amongst 979 patients with LSL, 12 patients with C-LSL were seen.Results: All lesions were tubulovillous adenomas with granular 0 – IIa + Is morphology. Median longitudinal extent was 95 mm (range 60 – 160), 58 % were located in the rectum, and 3 lesions (25 %) had complete circumferential involvement. EMR technical success was 100 %. There were no major adverse events. Symptomatic stricturing occurred in 2 cases (17 %) and was treated with endoscopic balloon dilation (median 4 sessions). Median follow up is 13 months. Minor residual adenoma was found in 7 (58 %) at first surveillance colonoscopy and was treated with snare excision. A total of 10 patients have completed a second surveillance colonoscopy with minor residual adenoma found in only 1 case. No patient required surgery or developed cancer in long-term follow-up.Conclusions: Endoscopic resection of C-LSL is feasible and safe. Minor residual adenoma is common but endoscopically treatable with long-term cure. Symptomatic stricturing amenable to balloon dilation may occur. Empiric surgical referral for C-LSL based on extensive circumferential involvement may be avoided.ClinicalTrials.gov NCT01368289